Antinomy of Multiple Interpretations of Very Urgent Reason in The Marriage Dispensation in Indonesia - Arkanbariq, Anantya Aliyya (Ahmad Dahlan Legal Perspective, 2024)
The purpose of this research is to analyze the purpose of marriage dispensation in Indonesia and the antinomy of multiple interpretations of very urgent reasons in the regulation of marriage dispensation in Indonesia. This research is an empirical normative research that focuses on examining the antinomy in the regulation of marriage dispensation in Indonesia based on primary and secondary data that has been determined. This research use conceptual approach, statutory approach, and case approach with descriptive-qualitative method. The research found that the reason for the existence of marriage dispensation in the Indonesian marriage legal framework is to provide a way out for couples who are forced to marry before the age of 19 due to urgent reasons. The research also found that there are at least two antinomies as result of the lack of clear parameters and guidelines for judges regarding the reasons for urgency, namely between legal certainty and justice and between expediency and judge objectivity. To suppress the existence of antinomies that are too extreme, at least the government must regulate several things as parameters and guidelines that limit judges in interpreting very urgent reasons, including certain circumstances that absolutely cannot be granted dispensation, the minimum age limit for granting marriage dispensation for marriages where no previous pregnancy has occurred, and judges must ensure that the prospective bride and groom are underage to understand the rights, obligations, and risks of being husband and wife. Therefore, this research contributes to the development of science, especially in the field of law, by discovering the existence of antinomy as a result of the broad authority of judges in interpreting the reasons that are very urgent in the regulation of marriage dispensation in Indonesia and providing solutions to overcome the antinomy that is too extreme on these issues.